2019
DOI: 10.1590/1980-549720190046
|View full text |Cite
|
Sign up to set email alerts
|

Consumo alimentar segundo o grau de processamento e características sociodemográficas: Estudo Pró-Saúde

Abstract: RESUMO: Objetivo: Investigar o consumo alimentar segundo o grau de processamento e associações com características sociodemográficas. Métodos: Estudo transversal de subamostra do Estudo Pró-Saúde, com 520 funcionários públicos de campi universitários, Rio de Janeiro, 2012-13. Questionário de frequência alimentar foi utilizado para classificar o consumo alimentar: 1) in natura, minimamente processados, preparações culinárias à base desses alimentos; 2) alimentos processados; 3) alimentos ultraprocessados. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
4
6
0
7
Order By: Relevance
“…One advantage is that Although, we found no statistically significant differences were found between the study groups at enrolment, including variables that are known to be associated with plasma glucose and UPF consumption, such as age, education and pre-pregnancy BMI. As such, the results should be interpreted in light of these considerations (1,2,(54)(55)(56)(57) .…”
Section: Resultsmentioning
confidence: 99%
“…One advantage is that Although, we found no statistically significant differences were found between the study groups at enrolment, including variables that are known to be associated with plasma glucose and UPF consumption, such as age, education and pre-pregnancy BMI. As such, the results should be interpreted in light of these considerations (1,2,(54)(55)(56)(57) .…”
Section: Resultsmentioning
confidence: 99%
“…In Australia, a cohort study found that mean change in BMI for both males and females was positively associated with the year of birth, where the prevalence of excess weight showed greater increases in cohorts born more recently than in older cohorts [ 27 ]. This cohort effect might be explained by dietary intake, given that younger individuals typically have a higher consumption of ultra-processed foods than older individuals [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berti et al, em seu estudo, verificaram que adultos mais jovens apresentaram maior consumo de ultraprocessados, hábitos alimentares não saudáveis, que na sua maioria são altamente calóricos e pobres em fibras, vitaminas e minerais, ressaltando a necessidade de intervenções principalmente nessa faixa etária, e indicando tendências futuras com implicações negativas na saúde dessa população 26 .…”
Section: Discussionunclassified